Analisis Sentimen Platform X Mengenai Pro Kontra Rekrutmen Guru Melalui Marketplace Menggunakan Metode Naïve Bayes - Yusuf Ramadhan Nasution; Aidil Halim Lubis; Tengku Fira Eliza (Bulletin of Computer Science Research, 2024)
Minister of Education, Culture, Research and Technology, Nadiem Anwar Makarim has discussed new breakthroughs regarding the teacher recruitment system through the marketplace. On May 24, 2024 since this policy was first presented, the teacher marketplace system has raised pros and cons in society. One of the social media that is busy discussing this topic is social media X. This research aims to conduct sentiment analysis of the opinions of Social Media X users regarding the teacher marketplace. Sentiment analysis was carried out by analyzing 640 opinion data. The data is classified using the Naive Bayes Method. The test results show that there are two classes in the test, namely positive and negative. This shows that platform X users who provide opinions are more pro towards this policy. Then, the data is divided, namely 90% training data and 10% test data. Based on the analysis that has been carried out, an accuracy value of 74%, precision 80%, recall 35%, and f-1 score 48% were obtained.